Digital transformation in asset-intensive organisations: The light and the dark side - Christoph Buck; John Clarke; Rui Torres de Oliveira; Kevin C. Desouza; Parisa Maroufkhani (Journal of Innovation & Knowledge (JIK), 2023)
Digital transformation has far-reaching effects on business and society. While the literature to date has mainly considered the positive opportunities associated with digital innovations at the consumer interface in terms of products and services, the impact on asset-intensive organisations has not yet been examined in detail. Because asset-intensive organisations have unique requirements, a focused approach is essential. This study provided an in-depth analysis of digital transformation efforts in asset-intensive organisations by interviewing elite informants in the field. Our results provide an explanatory model for the digital transformation of asset-intensive organisations from a dynamic process perspective. Our results also allowed us to uncover the dark side of digital transformation, and we theorise on its implications.
Keywords: M150; O320; O330; 650; Asset-intensive organisations; Dark side; Digital transformation; Digitalisation; Heavy industries